Critical nitrogen dilution curve and dry matter production parameters for several Mediterranean vegetables - De-Paz, José M.; Ramos, Carlos; Visconti, Fernando (Elsevier, 2022)
Inadequate nitrogen fertilizing practices lead to low nitrogen uptake efficiency (NUE), which increases water NO3− pollution, as well as N2O emissions to the atmosphere. In order to increase the NUE and decrease the N losses as NO3− and N2O from the soil-plant system, accurate data about optimum crop N concentrations and dry matter production throughout the growing season are still needed for many vegetables typically grown under Mediterranean climate. For this reason, several N fertilization trials were set up for globe artichoke, carrot, cauliflower, chard, chinese cabbage, early potato, leek, lettuce, onion, red cabbage, romanesco, and spinach, under the semiarid Mediterranean conditions of the Valencian Community (Eastern Spain) during several years. The fresh and dry matter weight (W), as well as the nitrogen concentration in the dry matter (%N) in both the marketable and non-marketable crop parts, was measured between 3 and 7 times throughout their respective growing seasons. The a and b coefficients of the average N dilution curve (%N = a W − b), for which all %N and W data were used, and the critical N dilution curve (%Nc = a Wc−b), for which only the minimun %N for maximum W data were used if available, in addition to the dry/fresh yield matter ratio (DM) and the harvest index (HI), were calculated for all these crops. No significant differences were observed between the average and critical N dilution curve coefficients in this work. Interestingly, the coefficients of both N dilution curves differed from the ones found in the literature with the exception of those obtained for similar cultivars, e.g., early potatoes, and under similar climatic conditions, i.e., Mediterranean. Besides, there were neither differences of DM and HI among the several N fertilization treatments. Therefore, due to the absence of changes in the N dilution curve and dry matter production coefficients for the different N supplies, all these parameters were estimated on the basis of the whole dataset, i.e., regardless of the N input. The use of the critical nitrogen dilution curve coefficients and dry matter production parameters presented in this work should contribute to better fit the N fertilizer additions to N demands of these vegetables under Mediterranean conditions, mainly, by their use through simulation models. Therefore, the NUE in horticulture should increase and the N losses as NO3− to inland and sea waters in these environments, and as N2O to the atmosphere should decrease.